3x^2-12x+39x=0

Simple and best practice solution for 3x^2-12x+39x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x^2-12x+39x=0 equation:



3x^2-12x+39x=0
We add all the numbers together, and all the variables
3x^2+27x=0
a = 3; b = 27; c = 0;
Δ = b2-4ac
Δ = 272-4·3·0
Δ = 729
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{729}=27$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(27)-27}{2*3}=\frac{-54}{6} =-9 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(27)+27}{2*3}=\frac{0}{6} =0 $

You can always share this solution

See similar equations:

| 10x-15-9x+21=7 | | 3x-2*3=x+8 | | 2x+7?=11 | | 21?16?l=14?421?16?l=14?4 | | ?x+3+?x=?x+8 | | 300x-170=250x+100 | | 3x=-0,4 | | 9(-x)=180 | | 1.2=w/6 | | 4^(2p-3)=64 | | -14+6y+7=1+4y | | 5-x+7x=-19 | | 4x+2x-3x+1=x+3 | | 8x8=40+ | | 2x+2(x-2)=10 | | 3(x-3)+4=4(x+7)+x | | z^2=10 | | 26-64=f | | 6x+2+6x=110 | | 3x/5/2=2 | | x^2+4x=120 | | X+X+10+(x+20)=360° | | 6-7v=-6v-3 | | X+X+10+(x+20)=360 | | -2-9f=5+9-7f | | 3=2x+3x+3 | | v+17?11=65 | | 1.69+2.1k=4.9k-9.38-4K | | X2+6x+30=0 | | -7z-10=10+3z | | -r+10=9r-10 | | 9.78+3.5u=-9.11+0.6u-0.25 |

Equations solver categories